Assessing student learning in designing instructional video: a case study - Syed Hassan, Sharifah Sariah (Malaysian Educational Technology Association, 2011)
The study of student learning in ICT learning environment has always obtained the centre stage for cooperative learning, self-reflection, and creative thinking that enhance higher order thinking skills. Student learning will be improved if a teacher adopted strategies of learning theories and effective student assessment. A pre-experimental design study was carried out as a one shot case study. The purpose of the study was to investigate the relationships of student-centred approach (strategies of instructions) that helps to stimulate self-regulation among students, metacognitive process towards student engagement. Quantitative and qualitative data collections have been adopted. A survey of 64 students was carried out at the end of the 12th week using a self-constructed questionnaire based on the previous related literatures. Qualitative data was based on discussion with other lecturer, blog entries from the students and personal journal entries. The triangulation was used to provide in depth understanding of the teaching process and their reflections on learning. The research provides information for further intervention in improving teaching strategies.